Root length: morphological indicator of Phaseolus vulgaris L. response to hydric stress in greenhouse - Amanda Martirena-Ramírez; Novisel Veitía; Damaris Torres; Leonardo Rivero; Lourdes R García; Raúl Collado; Miriam Ramírez- López (Biotecnología Vegetal, 2019)
Drought during the terminal phase of the crop is a global limitation for the production of common beans (Phaseolus vulgaris L.) and it is a problem that will be aggravated by the effects of climate change. The objective of this work was to select morphological indicators for hydric stress response in P. vulgaris in greenhouse. Four lines of brown grain and the commercial cultivar ‘BAT-93’ were evaluated. A water stress treatment was established where the irrigation was suspended in the pre-flowering stage until the harvest and a control with irrigation throughout the all crop cycle. Ten plants were random selected at each treatment and the angle of the basal roots, main root length (cm), the number of legumes/plant, the number of grains/legumes and the weight of 100 grains (g) were evaluated. Root length was a morphological indicator of the plants response to water stress under these conditions. It allowed to differentiate the response of the lines and cultivar ‘BAT-93’. The rest of the variables evaluated did not show significant differences between treatments. Root length is proposed as a morphological indicator of the response to water stress in the greenhouse that can be used in genetic improvement programs in P. vulgaris.